Postmodern Utopias and Feminist Fictions / [electronic resource] - Wagner-Lawlor, Jennifer A. (Cambridge : Cambridge University Press, 2013)
This study examines feminist speculative fiction from the late twentieth and early twenty-first century, and finds within it a new vision for the future. Rejecting notions of postmodern utopia as exclusionary, Jennifer A. Wagner-Lawlor advances one defined in terms of hospitality, casting what she calls 'imaginative sympathy' as the foundation of utopian desire. Tracing these themes through the works of Atwood, Butler, Lessing and Winterson, as well as those of well-known Muslim feminists such as El Saadawi, Parsipur and Mernissi, Wagner-Lawlor balances literary analysis with innovative extensions of feminist philosophy to show how inclusionary utopian thinking can inform and promote political agency. Examining these contemporary fictions reveals the rewards of attending to a community that acknowledges difference, diversity and the imaginative potential of every human being.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Utopias in literature; Feminism and literature; Postmodernism (Literature)